Marcos Martínez Hernández, Semántica del griego antiguo, Madrid, Ediciones Clásicas, 1997, 326 pp. (Minerva, 2019)
Review: Marcos Martínez Hernández, Semántica del griego antiguo, Madrid, Ediciones Clásicas, 1997, 326 pp.